Measurement of the τ Michel parameters η and ξκ in the radiative leptonic decay τ^- → ^- ν_τ ν_γ. (24th February 2018) - Shimizu, N; Aihara, H; Epifanov, D; Adachi, I; Al Said, S; Asner, D M; Aulchenko, V; Aushev, T; Ayad, R; Babu, V; Badhrees, I; Bakich, A M; et al.
Abstract: We present a measurement of the Michel parameters of the τ lepton, η and ξκ, in the radiative leptonic decay τ^- → ^- ν_τ ν_ γ using 711 fb^-1 of collision data collected with the Belle detector at the KEKB e^+e^- collider. The Michel parameters are measured in an unbinned maximum likelihood fit to the kinematic distribution of e^+e^-→τ^+τ^-→ (π^+π^0 ν_τ)(^-ν_τν_γ) (=e or μ) . The measured values of the Michel parameters are η = -1.3 ± 1.5 ± 0.8 and ξκ = 0.5 ± 0.4 ± 0.2, where the first error is statistical and the second is systematic. This is the first measurement of these parameters. These results are consistent with the Standard Model predictions within their uncertainties, and constrain the coupling constants of the generalized weak interaction.